2013
DOI: 10.1159/000354503
|View full text |Cite
|
Sign up to set email alerts
|

Gestational Undernourishment Modifies the Composition of Skeletal Muscle Transverse Tubule Membranes and the Mechanical Properties of Muscles in Newborn Rats

Abstract: Backgroud/Aims: Skeletal muscle (SM) constitutes more than 40% of the body weight in adulthood. Transports dietary glucose mainly through the insulin-dependent glucose transporter (Glut-4) located in the Transverse tubule membrane system (TT). The TT development ends shortly after birth. The TT membrane hosts the proteins involved in excitation-contraction coupling and glucose uptake. Glycaemic regulation through movement is a key function of fully developed skeletal muscle. In this study, we aimed to characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
(62 reference statements)
0
1
0
Order By: Relevance
“…To explain the increased normalized force of UM muscles it is suggested that undernutrition provokes a reduction in the activity of the Ca 2+ ATPase (SERCA) in the sarcoplasmic reticulum which induces an increment in the calcium availability during the contraction of muscle fibres at early post‐natal ages, as recently proposed by Ramirez‐Oseguera et al. () in the newborn undernourished rat. In addition, it is known that hypoproteic diets induce a reduction of antioxidants, such as glutathione, in the fast muscles of rats (Plant et al., ; Akinola et al., ).…”
Section: Discussionmentioning
confidence: 96%
“…To explain the increased normalized force of UM muscles it is suggested that undernutrition provokes a reduction in the activity of the Ca 2+ ATPase (SERCA) in the sarcoplasmic reticulum which induces an increment in the calcium availability during the contraction of muscle fibres at early post‐natal ages, as recently proposed by Ramirez‐Oseguera et al. () in the newborn undernourished rat. In addition, it is known that hypoproteic diets induce a reduction of antioxidants, such as glutathione, in the fast muscles of rats (Plant et al., ; Akinola et al., ).…”
Section: Discussionmentioning
confidence: 96%